Isolable arene sandwiched copper(i) pyrazolates. (18th May 2015) - Jayaratna, Naleen B.; Hettiarachchi, Champika V.; Yousufuddin, Muhammed; Rasika Dias, H. V.
Abstract : The π-acidic, trinuclear, copper(i ) pyrazolate [3, 5-(CF3 )2 Pz]Cu3 reacts with simple π-basic aromatic hydrocarbon compounds forming sandwich complexes of various types. Abstract : The π-acid/π-base adducts of [3, 5-(CF3 )2 Pz]Cu3 [Cu3 ] and benzene[Bz], mesitylene[Mes] and naphthalene[Nap] have been isolated. They form columnar structures of the type[Bz][Cu3 ]2 ∞, [Mes][Cu3 ]∞ and[Nap][Cu3 ]∞ in the solid state, and are luminescent.